Development Status and Trends of Space Processor - Zhigang YU; Xu FENG; Zhou LU; Jixing GAO; Wenhui DING (天地一体化信息网络)
Space electronic system is the ＆quot;brain＆quot; of aerospace engineering models and the core fi eld of competitive development of major countries around the world.As the most core device in space electronic system, space processor directly aff ects the performance, reliability and safety of aerospace models.On the basis of brief introduced of space electronic systems, fi rstly, the development status of foreign space processors was analyzed, and then the development roadmap of space processors such as SPARC, PowerPC, ARM, RISC V, etc were combed and formed.The development process was summarized into three stages:initial stage, development stage and new stage, considered architecture and performance parameters.Finally, the development trend of space processors in the future was summarized as ＆quot;fi ve modernizations＆quot;: micro system, commercialization, intelligent, ecological and cloud enabled.